Effect of salinity and light intensity on the growth of chattonella (raphidophyceae) - Lee, Sze Wan (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Harmful algal bloom is a natural phenomenon referring to drastic increase in abundance of phytoplankton. In Malaysian water, Chattonella spp. are members of the Raphidophytes that previous reported as harmful algal that associated with bloom event in Johor in 2002. In this study, clonal culture of Chattonella from Santubong (CtSb02) estuary was used to investigate its salinity tolerance, growth at different light intensity and also morphological changes at different light intensity. For salinity experiment, medium with salinity from 5 PSU to 35 PSU was prepared by diluting filtered seawater with deionized distilled water to desired salinities. The highest specific growth rate was 0.276 day"I in 25 PSU. Optimum salinity 25 PSU medium was chosen and proceeded with growth experiment at different light intensity. Light intensity was varied from 0 /lmol photons m02 sol, 50 IJ.mol photons m02 sol, 100 /lmol photons m02 sol, 200 IJ.mol photons m02 sol and 300 Ilmol photons m02 sol .300 J.Lmol photons m02 sol shown highest specific growth rate 0.417 day"l. The result of chlorophyll shown that the higher the irradiance, lower the concentration of chlorophyll and the location of chlorophyll in outer layer area of cell.